PENGEMBANGAN MANAJEMEN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN MUTU PENDIDIKAN - Tahir, Wahid (Inspiratif Pendidikan, 2017)
Increasing human resources is becoming increasingly important for institutions that are used to gain better control through their own business. Institutions should demonstrate that they are able to provide quality education to learners. For every institution, quality is the main agenda and quality improvement is the most important task. Nevertheless, some people think of quality as a concept full of riddles. Quality is regarded as confusing and difficult to measure. Quality in a person’s view is sometimes different from that of others. So it is not strange if experts do not have the same conclusions about how to create good and quality institutions. Human resource management in quality improvement aims to change the institution that operates it into a sincere team, without conflict and internal competition, to achieve a single goal, namely to satisfy customers.